Take your shoes off to reduce patellofemoral joint stress during running. Issue 6 (13th July 2013) - Bonacci, Jason; Vicenzino, Bill; Spratford, Wayne; Collins, Paul
Abstract : Aim: Elevated patellofemoral joint stress is thought to contribute to the development and progression of patellofemoral pain syndrome. The purpose of this study was to determine if running barefoot decreases patellofemoral joint stress in comparison to shod running. Methods: Lower extremity kinematics and ground reaction force data were collected from 22 trained runners during overground running while barefoot and in a neutral running shoe. The kinematic and kinetic data were used as input variables into a previously described mathematical model to determine patellofemoral joint stress. Knee flexion angle, net knee extension moment and the model outputs of contact area, patellofemoral joint reaction force and patellofemoral joint stress were plotted over the stance phase of the gait cycle and peak values compared using paired t tests and standardised mean differences calculated. Results: Running barefoot decreased peak patellofemoral joint stress by 12% (p=0.000) in comparison to shod running. The reduction in patellofemoral joint stress was a result of reduced patellofemoral joint reaction forces (12%, p=0.000) while running barefoot. Conclusions: Elevated patellofemoral joint stress during shod running might contribute to patellofemoral pain. Running barefoot decreases patellofemoral joint stress.